Procyclical leverage in Europe and its role in asset pricing - Markus Baltzer; Alexandra Koehl; Stefan Reitz (Deutsche Bundesbank, 2019)
Broker-dealer leverage has recently proven to be strongly procyclical, exhibiting impressive explanatory power for a large cross-section of asset returns in the US. In this paper we add empirical evidence to this finding, showing that European and German broker-dealers actively manage their balance sheets. Moreover, by applying standard Fama-MacBeth regressions as well as dynamic asset pricing models (Adrian, Crump, and Moench, 2015), we confirm the importance of brokerdealer balance-sheet indicators for asset pricing. In particular, leverage shows a procyclical behavior with a positive price of risk. Moreover, high leverage coincides with high asset prices, thereby forecasting lower future returns.
Keywords: E31; G21; 330; broker-dealer leverage; intermediary asset pricing; dynamic asset pricing